PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH PERKOTAAN DI KABUPATEN KOTABARU (Studi Kasus di Kecamatan Pulau Laut Utara) - Siti Rabiatul Adawiah; Yudi Firmanul Arifin; Muchtar Effendy; Machfudz Siddiq (EnviroScienteae, 2011)
The aims of the research were to identify and describe the form of the community’s participation in the waste management of urban area in the Kotabaru Regency; to know the community’s participation level for the waste management of urban areas; and to know the affecting factors the community’s participation for the waste management of urban areas. The research was conducted in Kotabaru Regency. The sampel village was determined purposively, namely semayapVillage, North Sea Island Subdistrict. Where was included the ragion of the waste management for the urban Development and Housing Service Kotabaru Regency, with the most densely number of inhabitant and household. Data collection used survey and interview method. Sampling was in accidental method on 10% of the total sample populationin the three of the most densely neighbourhood associations (RT) on the sample village. The results showed that the community’s participation in the waste management of urban areas in the Kotabaru Regency observed to community activity related with the cleanliness of the residence and the environment around, covered three stages, namely planning, the implementation and the supervision. The community’s participation for the waste management of urban areas in the Kotabaru Regency, totally dominant was classed as moderate to high, and very few be classed as low, so as the hypothesis that the level of the community's participation in the waste management of urban areas in the Kotabaru Regency still was classified as low could be refused. The community’s participation level for the waste management of urban areas was significantly affected by formal education level and the government institution role, but that was not affected by age and household income.